Effect of biodegradation on the physical properties of palm oil mill effluent (POME) using mixed culture of fungi - Alade, Abass O.; Jameel, Ahmed Tariq; Muyibi, Suleyman A.; Abdul Karim, Mohamed I.; Alam, Md. Zahangir (Kulliyyah of Engineering, IIUM, 2013)
This study investigated the effects of biodegradation by the mixed culture of fungi (Pithomyces sacchari and Pestalotiopsis maculans) on selected physical properties of palm oil mill effluent (POME). Mixed culture innoculum (4% v/v) was added to autoclaved and raw POME samples, which were subjected to biodegradation at 120rpm and 350 C for six days. The pH, electrical conductivity, salinity, total dissolved solids and biosolids of the digested samples were quantified at 24h intervals. The values of pH, electrical conductivity, salinity, total dissolved solids and biosolids for the autoclaved POME sample, at the end of the digestion period, were 6.88, 4.38mS/cm, 2.33‰, 2.28 g/l and 25.6g/l, respectively, and these were higher than 6.34, 4.24mS/cm, 2.23‰, 2.22 g/l and 22.87g/l obtained for the raw POME sample, respectively. The kinetic studies, based on the degradation of the biosolids, shows that the rate constants (K0= 0.7mgl-1min-1 and K1= 0.4 min-1) of the zero and first order models, respectively, of the autoclaved POME sample were higher than the rate constant (K0= 0.03 mgl-1min-1 and K1= 0.02 min-1) obtained for raw POME sample. This indicates that the mixed culture experienced inhibition in the raw POME sample.